Heutagogy and self-determined learning: a review of the published literature on the application and implementation of the theory. (2nd September 2019) - Agonács, Nikoletta; Matos, João Filipe
ABSTRACT: Heutagogy is described as an extension to andragogy and has also been referred to as a potential theory for online and distance education. There have been reviews of the literature on heutagogy, albeit the research field seems to lack a review that would provide a map of research studies revealing clear empirical evidence of the application of the theory. The aim of this study is to understand what empirical evidence exists when it comes to putting heutagogy in practice, the state of the art of the research field and to identify possible gaps. Employing a purposeful sampling strategy, the final corpus was selected through a two-step filtering process. Heutagogical principles were used as categories for analysis with the pedagogy–andragogy–heutagogy continuum providing an additional category. This study makes a significant contribution to the research field of heutagogy inasmuch as it identified that (i) the categories of capability development and non-linearity are underrepresented; (ii) there is a predominance of qualitative methods and lack of quantitative statistical data and longitudinal data collection methods; (iii) the geographic and cultural distribution of researchers and the selected sample size are limited; (iv) heutagogy has been preponderantly applied along with online or digital technological components.